Clinical effectiveness of telmisartan alone or in combination therapy for controlling blood pressure and vascular risk in the elderly - Jugdutt, Bodh I (Dove Medical Press, 2010)
Elderly patients (age ≥65 years) with hypertension are at high risk for vascular complications, especially when diabetes is present. Antihypertensive drugs that inhibit the renin-angiotensin system have been shown to be effective for controlling blood pressure in adult and elderly patients. Importantly, renin-angiotensin system inhibitors were shown to have benefits beyond their classic cardioprotective and vasculoprotective effects, including reducing the risk of new-onset diabetes and associated cardiovascular effects. The discovery that the renin-angiotensin system inhibitor and angiotensin II type 1 (AT(1)) receptor blocker (ARB), telmisartan, can selectively activate the peroxisome proliferator-activated receptor-γ (PPARγ, an established antidiabetic drug target) provides the unique opportunity to prevent and treat cardiovascular complications in high-risk elderly patients with hypertension and new-onset diabetes. Two large clinical trials, ONTARGET (Ongoing Telmisartan Alone in combination with Ramipril Global Endpoint Trial) and TRANSCEND (Telmisartan Randomized AssessmeNt Study in ACE-I iNtolerant subjects with cardiovascular disease) have assessed the cardioprotective and antidiabetic effects of telmisartan. The collective data suggest that telmisartan is a promising drug for controlling hypertension and reducing vascular risk in high-risk elderly patients with new-onset diabetes.